The development of style in Malaysian printmaking: 1930-2000 / Mohd Jamil Mat Isa - Mat Isa, Mohd Jamil (Institute of Graduate Studies, UiTM, 2018)
The development of printmaking started as a medium of communication, be it a religious propaganda or as a tool to achieve independence. Printmaking can be classified into several categories, such as relief printing, intaglio, planographic and now in the modern era, is a digital print. Malaysian printmaking has been developing since the Colonial Era (1930s) by Chuah Thien Teng and Abdullah Ariff. Woodcut and linocut are the techniques chosen by them. Later on, other artists explored the medium; they applied more techniques included the latest digital technology. The objectives of this study are to trace on the development of style in Malaysian printmaking, to identify the factors that influence the development of style in Malaysian printmaking and to document the historical development of Malaysian printmaking. This research will use qualitative methods with art historical approach based on the primary and secondary data. The data collected in the form of text from books, exhibition catalogues, and art auction catalogues. The works of printmaking are divided into two main categories, namely the Pre-Independence Era (1930-1957) and Post-Independence Era (1958-2000)…